2021
DOI: 10.4193/rhin21.059
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a brief version of the Questionnaire of Olfactory Disorders (brief QOD) in patients with olfactory dysfunction

Abstract: Background: The aim of this study was to determine the reliability and validity of the brief version of Questionnaire of Olfactory Disorders (brief QOD). Methods: A total of 372 patients participated in this study. Olfactory function was examined using the Sniffin’ Sticks test. The brief version of QOD, including 4 items concerning parosmia (QOD-P), 7 items concerning quality of life (QOD-QOL), and 3 visual analog scales to rate disease burden, awareness of the disorder and issues related to professional life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…As mentioned in the introduction, a number of studies have now looked at the ODQ or derivations of it. Zou et al 25 studied 372 participants with olfactory dysfunction and included threshold, discrimination, identification scores from the Sniffin’ Sticks along with results of the brief version of the ODQ. They showed that olfactory function was found to be associated with parosmia, quality of life and VAS subsections of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, a number of studies have now looked at the ODQ or derivations of it. Zou et al 25 studied 372 participants with olfactory dysfunction and included threshold, discrimination, identification scores from the Sniffin’ Sticks along with results of the brief version of the ODQ. They showed that olfactory function was found to be associated with parosmia, quality of life and VAS subsections of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, a number of studies have now looked at the ODQ or derivations of it. Zou et al 25 studied 372 participants with olfactory dysfunction and included threshold, discrimination, identification scores from the Sniffin'…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quality of life was evaluated using the brief version of the Questionnaire of Olfactory Disorders (brief QOD) [43]. This questionnaire consists of 14 items related to patient-reported outcomes in olfactory-speci c quality of life (QOD-QOL, 7 items), parosmia (QOD-P, 4 items) and 3 different visual analogue scales (QOD-VAS).…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Despite the significant impact of OD on patients’ quality of life, there is currently only one validated specific instrument available to assess it in individuals with olfactory dysfunction: the Questionnaire of Olfactory Disorders (QOD), which exists in both a full length 8 and a short version 9 . Proposed in 2005 by Frasnelli and Hummel 8 , QOD is a self-administered instrument designed specifically to assess the impact of OD on patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%